Terapia familiar focada na emoção para o treinamento de cuidadores de indivíduos com transtornos alimentares: análise de entrevista com profissionais de saúde mental - Francisco, Caroline Pozzobon (2022)
Eating Disorders (EDs) are considered complex because of the difficulties faced by professionals and families in the overall treatment of patients with this diagnosis. These difficulties are pointed out in the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) and in several studies on EDs. Due to its complexity, many studies have been done over time to improve clinical practice in the management of these disorders, and a relevant factor raised by these studies is the importance of emotional regulation and guidance for parents of youngsters with ED. The Maudsley Method emerged with the intention of bringing together these relevant factors and developing a new protocol for outpatient treatment for these cases. In this sense, this study aimed to identify with mental health professionals who work with ED the forms of training and application of the Maudsley Method. With emphasis on the psychoeducation of animal metaphors for the identification and modification of maladaptive strategies of caregivers of adolescents with some ED. The study was developed in a sample composed of seven individuals of both sexes, aged between 27 and 52 years, belonging to professions in the mental health area, with experience in ATs. The instrument used was a structured interview in questionnaire format. The data obtained through the interviewees, as an improvement in the caregivers' understanding of EDs and their coping styles, regarding the gains of applying the Maudsley method are also observed by the results of clinical studies and meta-analyses conducted outside Brazil.